Comprehensive performance study of aluminum ash and calcium carbide slag for brick making under ultra-high pressure. (12th December 2022) - Ren, Yuanchuan; Wang, Zuoliang; Qu, Guangfei; Kuang, Lingrui; Ning, Ping; Ren, Nanqi; Zhang, Chaoneng; Chen, Xiuping; Wu, Fenghui; Hu, Yan; Wang, Jun; Lu, Ping; et al.
Graphical abstract: Highlights: Ultra high pressure contact forming technology. Preparation of high performance building materials from aluminum ash and carbide slag. The compressive strength and flexural strength of bricks are 75 MPa and 3.6 MPa respectively. It provides a feasible idea for the harmless and resourceful treatment of bulk solid wastes. Abstract: Aluminum ash is a large amount of industrial solid waste produced by the electrolytic aluminum industry, and calcium carbide slag is an alkaline industrial solid waste produced by the energy industry. Both of them will cause serious pollution risks to the environment. Its harmless and resource-based treatment has become one of the main research directions. In this paper, the ultra-high pressure contact molding technology is used for the first time to prepare high-performance building materials with aluminum ash and calcium carbide slag as raw materials. The changes of mechanical properties and waterproof properties of bricks under different proportion, pressing pressure, curing time and curing conditions were investigated. Finally, the leaching toxicity was investigated. The experimental results show that the best ratio of aluminum ash and calcium carbide slag is 1:9, the best pressure is 300mpa, the best curing time is 5d, and the best curing condition is natural curing. The compressive strength and flexural strength of the brick are about 75 MPa and 3.6 MPa respectively, and the softening coefficient is about 0.99. This shows that the bricks formed by ultra-high pressure contact have high mechanical properties and waterproof properties, and the leaching toxicity meets the class V water quality standard in the environmental quality standard for surface water (GB3838-2002). The brick was characterized by SEM, EDS, XRD and particle size analysis. By further exploring its comprehensive properties, it is proved that ultra-high pressure contact molding is feasible in the resource utilization of aluminum ash and calcium carbide slag. This study provides a feasible idea for the harmless and resource treatment of bulk solid waste, simulate the change of minerals under surface pressure in the earth's crust, providing a research path for the solidification and stabilization of pollutants.